A Comparison of Heat Storage Densities of Zeolite Granulates Predicted by the Dubinin-polanyi Theory to Experimental Measurements. (May 2017) - Lehmann, Christoph; Beckert, Steffen; Nonnen, Thomas; Möllmer, Jens; Gläser, Roger; Kolditz, Olaf; Nagel, Thomas
Abstract: Thermochemical heat storage devices based on water adsorption on microporous materials are a viable option for heat storage applications. The Dubinin-Polanyi theory of micropore filling has been widely applied for the thermodynamical characterization of various adsorption working pairs. It has been used for the deduction of adsorption enthalpies from adsorption equilibrium data. How well the theory predicts the dependence of storage densities on the storage cycle characteristics remains to be clarified as it is vital for technology assessment and design. This study compares the heat storage densities predicted by the Dubinin-Polanyi theory to experimentally determined data of two granulated zeolite samples, namely a Na-X and a Ca-X, under various humidity conditions.